Automatic Production and Preliminary PET Imaging of a New Imaging Agent [18F]AlF-FAPT - Huang, JiaWen; Fu, LiLan; Hu, KongZhen; Huang, Shun; Han, YanJiang; Lin, Run; Xu, WanBang; Tang, Ganghua; Huang, Yonghui (Frontiers in Oncology, 2022)
Background: Fibroblast activating protein (FAP) has become an important target for cancer diagnostic imaging and targeted radiotherapy. In particular, [18F]FAPI-42 has been successfully applied to positron emission tomography (PET) imaging of various tumors. However, it exhibits high hepatobiliary metabolism and is thus not conducive to abdominal tumor imaging. This study reports a novel 18F-labeled FAP inhibitor, [18F]AlF-FAPT, a better FAPI imaging agent than [18F]FAPI-42. Materials and methods: The precursor of [18F]AlF-FAPT (NOTA-FAPT) was designed and synthesized using the standard FMOC solid phase synthesis method. [18F]AlF-FAPT was subsequently synthesized and radiolabeled with 18F using the AllInOne synthesis module. Dynamic MicroPET and biodistribution studies of [18F]AlF-FAPT were then conducted in xenograft tumor mouse models to determine its suitability. Results: The precursors NOTA-FAPT were obtained with a chemical purity of > 95%. [18F]AlF-FAPT was synthesized automatically using the cassette-based module AllInOne within 40 min. The non-decay corrected radiochemical yield was 25.0±5.3% (n=3). In vivo imaging and biodistribution studies further demonstrated that compared with [18F]-FAPI-42, [18F]AlF-FAPT had a lower hepatobiliary uptake than [18F]FAPI-42, which was advantageous for imaging abdominal tumors. Conclusion: [18F]AlF-FAPT can be synthesized automatically using a one-step method of aluminum fluoride. Collectively, [18F]AlF-FAPT is a better FAPI imaging agent than [18F]FAPI-42. This study proves the feasibility of using [18F]AlF-FAPT as a new radioactive tracer for PET imaging.